The virtual Middle East Seismographic Network (vMESN); Concept and Implementation - Ghalib, Hafidh A. A.; Aleqabi, Ghassan I.; Khudhur, Fadhil I.; Al-Yazjeen, Tawfiq; Al-Qaryouti, Mahmoud (Sulaimani Journal for Pure and Applied Sciences, 2016)
At the 7th Gulf Seismic Forum on January 22-25, 2012, Jeddah, Saudi Arabia, Ghalib et al. (2012) proposed the establishment of vMESN. It is a virtual seismographic network that all Middle East countries operating telemetered seismic stations can equally exploit to monitor earthquakes in and around their respective territories. The overarching goal of vMESN is to advance the teaching and practice of seismology and research among member countries. It is a scientifically and economically rewarding concept with high return on modest investment in resources and infrastructure. It is also technically feasible to implement at member data centers to greatly improve the capability and coverage of their national networks when augmented with international stations in the region. The integrated real-time data that vMESN provides is invaluable for research and development in seismology and earthquakes engineering. Presently, vMESN is implemented and operational at Jordan, Erbil and Sulaimaniyah Seismological Observatories (JSO, ESO and SSO, respectively) and at Array Information Technology (AIT) data center in Maryland, USA. At no cost to the host and member countries, AIT is contributing real-time data from the international stations in the region; Jordan is contributing real-time data from their Jordan Seismological Network (JSN), and Kurdistan from their KSIRS array and some of the North Iraq Seismographic Network (NISN) stations. Three-component data from a total of 72 stations is currently being automatically shared and independently processed at the aforementioned data centers. The Antelope, and soon SeisComp3, real-time software system is configured to automatically acquire, forward and process the data. The invitation is open to all countries in the Middle East to join vMESN, if they commit to the requirement of sharing data in real-time over Internet. Each member country continues to maintain full control over their networks’ data and over what to acquire and forward to others. Also, each member country continues to independently process the data and publishes bulletins in accordance with its technical practices, standards and regulations.
Keywords: vMESNMiddle Eastearthquakesseismographicnetwork